Influence of Ru3+ ions at Al/GaAs interface on Schottky diodes - Mazari, H.; Benamara, Z.; Ameur, K.; Benseddik, N.; Bonnaud, O.; Olier, R.; Gruzza, B. (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol vol. 1; issue 1, 2008 & vol. 2; issue 1 & 2, 2009.